O herói na literatura juvenil de Moacyr Scliar - Schneider, Talita Felix (2012)
This dissertation presents the theme of the literary youth of Moacyr Scliar, focusing on the kinds of hero in these narratives. Using the literature as a methodology, it appears like the heroes of Scliar contribute to the formation of the young reader. At first, it exposes the theoretical concepts that include youth, literature and the hero. Soon after, we describe the biographical aspects of the author and the story of his youth books. As a closingm there us te analysis of the trajetory of the heroes and how is the process of humanization. The theory behind this study includes authors such as Luís Groppo, Edgar Morin, João Luís Ceccantini, Regina Zilberman, Jaime Padrino, Lutz Müller, Carol Pearson, Joseph Campbell. The juvenile literature created by Scliar is configured as a true voyage of discovery to the extent that their heroes, complete their journeys, their mature dragons and discover themselves. The literature, therefore, appears as a means of humanizing the young hero.